Social components of food marketing in RDP–supported projects - Augustyn, Anna; Nemes, Gusztáv (Socio.hu Társadalomtudományi Szemle, 2016)
In response to a growing awareness of the consumers across Europe, efforts towards improvements of food marketing have been intensifying during the last decades. Targeted actions to tackle these challenges have been undertaken by rural communities, public and private sector, including large multi–national companies. This paper looks at the various approaches fostered within the EU Rural Development Programmes. We review different types of marketing schemes relevant for EU rural areas, affected by both market and public sector mechanisms. Social components have been frequently added to these, based on voluntary, bottom–up processes and quality control, and embedded in local community and economic development. We claim that social marketing can be effectively combined with the public support available under the EU rural development policy and help food producers to gain better access to markets. The value that social networking and bottomup rural development represent in the marketing of local products is essential for food–driven innovation in rural areas. Our paper presents an analysis of projects from the database of the European Network for Rural Development, clustered around different social marketing components. Key words: social marketing, rural development, Common Agricultural Policy, standards